Body size performance (shoulder height, body length, and chest size) of Murrah Buffalo - Alvin Syah Muhammad Noor; Didin Supriat Tasripin; Bambang Kholiq Mutaqin (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
The research on the body measurements of female and male Murrah Buffalo was carried out in December 2023 on Pagar Merbau Subdistrict, Deli Serdang Regency, North Sumatra. The research aimed to know body measurements, including shoulder height, body length, and chest size, of Murrah Buffalo which were aged <1.5 years old, 1.5-3.5 years old and >3.5 years old on Pagar Merbau Subdistrict. The number of buffalo studied was 113, including 99 female buffalo and 14 male buffalo. The research method uses a descriptive quantitative method with a case study approach. Data collection uses the snowball sampling technique. The results showed that the averaged shoulder height of Murrah Buffalo females aged <1.5 years old, 1.5-3.5 years old and >3.5 years old were 89.82±15.77 cm, 124.67±3.25 cm, and 135.65±6.24 cm; in males, they were 84.79±16.40 cm, 121 cm, and 147 cm, respectively. Meanwhile, the average body length in females was 83.50±26.74 cm, 122.73±2.92 cm, and 131.26±6.23 cm; in males, it was 89.67±23.04 cm, 119 cm, and 151 cm, respectively. Furthermore, the average chest size in females was 102.82±24.73 cm, 189.15±13.76 cm, and 202.61±12.24 cm; in males, it was 106.33±26.13 cm, 201 cm, and 209 cm. The conclusion is that the body size of the Murrah buffalo in Pagar Merbau District, Deli Serdang Regency, is relatively proportional to the body size of the cheap buffalo.